2022
DOI: 10.1136/bmjopen-2022-067838
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram models to predict low fertilisation rate and total fertilisation failure in patients undergoing conventional IVF cycles

Abstract: ObjectivesTo establish visualised prediction models of low fertilisation rate (LFR) and total fertilisation failure (TFF) for patients in conventional in vitro fertilisation (IVF) cycles.DesignA retrospective cohort study.SettingData from August 2017 to August 2021 were collected from the electronic records of a large obstetrics and gynaecology hospital in Sichuan, China.ParticipantsA total of 11 598 eligible patients who underwent the first IVF cycles were included. All patients were randomly divided into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…It is known that female factors such as the oocyte quality and quantity, age, and hormone levels can all affect the IVF outcome of in vitro fertilization. Wang et al reported that a nomogram model combined both male parameters and female reproductive indicators was constructed to produce convenient prediction models of poor fertilization and fertilization failure [ 29 ]. The effects of technique, equipment and skill levels of IVF performers were not considered either.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that female factors such as the oocyte quality and quantity, age, and hormone levels can all affect the IVF outcome of in vitro fertilization. Wang et al reported that a nomogram model combined both male parameters and female reproductive indicators was constructed to produce convenient prediction models of poor fertilization and fertilization failure [ 29 ]. The effects of technique, equipment and skill levels of IVF performers were not considered either.…”
Section: Discussionmentioning
confidence: 99%